An unusual case of angioleiomyoma of the vocal cord in a patient with oral cancer - Munnangi, Ashwini; Buggaveeti, Rahul; Budharapu, Abhishek; Reddy, Vinila Belum; Chennamchetty, Vijay Kumar; Nayak, Umanath K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Angioleiomyomas, as the name suggests, are tumors arising from smooth muscle of vascular tissue. We report a case of angioleiomyoma arising from the right vocal cord in a 45-year-old male with a history of squamous cell carcinoma (SCC) of the oral cavity who had restricted mouth opening owing to previous surgery and adjuvant radiation therapy because of which accessing the vocal cord tumour was difficult by conventional laryngoscopy. Initial bronchoscopy guided excision of the tumour was done. After a month, an emergency tracheostomy had to be performed as he presented with stridor due to recurrence of tumour. Laryngofissure was performed and tumour was excised. The patient is on regular follow up with no recurrence of tumour. We present in this case report, the clinical presentation, diagnosis, management options, pathological features and outcomes of this rare entity known as laryngeal angioleiomyoma.